Description of Social Emotional Skills as a Precondition for building Elementary School Students' Social Awareness Characters - Rizkiya, Lina Marlina Nur; Hakam, Kama Abdul; Agustin, Mubiar (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This research is motivated by the desire to see the extent of social emotional skills in elementary school students, given that one of the programs introduced by the ministry of education regarding freedom of learning. One important point in the program is that the assessment is carried out not only on cognitive aspects but also on students character, where it is an output from having good social emotional skills. This is in line with the competencies that should be possessed in the 21st century. Social emotional skills themselves refer to the ability to regulate one's thoughts, emotions, and behavior so that these skills are a precondition for having good characters, especially social awareness in elementary school. This research uses descriptive analysis method. Data were collected through student observation, interviews with teachers and analysis of teacher’s learning journals. The results of the analysis show that the social skills possessed by students are: (1) the ability to think applicatively in terms of regulating the thoughts and emotions of students has not been running together (2) students tend not to be able to control their emotions when interacting with peers (3) the character of social awareness still has not reflected in students' daily lives. The results of this study are expected to be used as a consideration in developing learning that teaches about social emotional skills